Teachers’ Perception on the Implementation of Problem-Based Learning Integrated with Predict Observe Explain on Students’ Critical Thinking Skills - Nurhayati, Nurhayati; Rusyati, Lilit; Rustaman, Nuryani (FKIP - Universitas Riau, 2025)
Science education in phase D aims to develop scientific attitudes, one of which is critical thinking skills. To achieve this, it is necessary to implement learning that can foster critical thinking skills and encourage active student participation. This study examines the application of integrated problem-based learning (PBL-POE) and its relationship to students' critical thinking skills. The method used is qualitative case study research. The subjects of this study were four science teachers at a public junior high school in Bandung. Data was collected through interviews. Data analysis was based on an interactive model, including data collection, data condensation, data presentation, data verification, and conclusion drawing. The results of the study indicate that problem-based learning and PBL-POE have not been implemented in the school. One of the factors influencing this is teacher competence. Regarding critical thinking skills, each teacher has their own views on the skills that need to be developed by students, but these have not been implemented in PBL-POE learning. The relationship with critical thinking skills has not yet been established because PBL-POE has not yet been implemented, so no correlation or data on this relationship has been found.